Cyclic esotropia - Akhanda, AH; Ahmed, T; Quayum, MA; Wahab, MA (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):60-2.The abstract of this article is available on the PubMed website